Early-onset group B streptococcal disease in African countries and maternal vaccination strategies - Dangor, Ziyaad; Seale, Anna C.; Baba, Vuyelwa; Kwatra, Gaurav (Frontiers in Public Health, 2023)
Invasive group B streptococcal (GBS) disease is the commonest perinatally-acquired bacterial infection in newborns; the burden is higher in African countries where intrapartum antibiotic prophylaxis strategies are not feasible. In sub-Saharan Africa, almost one in four newborns with GBS early-onset disease will demise, and one in ten survivors have moderate or severe neurodevelopmental impairment. A maternal GBS vaccine to prevent invasive GBS disease in infancy is a pragmatic and cost-effective preventative strategy for Africa. Hexavalent polysaccharide protein conjugate and Alpha family surface protein vaccines are undergoing phase II clinical trials. Vaccine licensure may be facilitated by demonstrating safety and immunological correlates/thresholds suggestive of protection against invasive GBS disease. This will then be followed by phase IV effectiveness studies to assess the burden of GBS vaccine preventable disease, including the effect on all-cause neonatal infections, neonatal deaths and stillbirths.